(untitled) (Nigerian Journal of Technology, 2018)
This paper propose a Pilot Symbol Assisted Modulation (PSAM) channel estimation and compensation technique for rectangular M-QAM based on Cubic interpolation in order to determine the channel state information (CSI) over flat Rayleigh fading channels. The proposed Cubic channel estimator technique is based on sliding window approach and pilot symbol estimates adjustment in order to reduce its computational time complexity. The Cubic estimator is combined with the Koetter and Vardy (KV) Reed-Solomon (RS) decoder to test its performance. The simulation results show that the Cubic interpolation gives the same performance as the Linear, and Sinc interpolators over slow flat Rayleigh fading channel; however, it achieves significant performance improvement of +1.0dB in symbol error rate (SER) over fast flat Rayleigh fading channel.